Speeding up NMR by in Situ Photo‐Induced Reversible Acceleration of T1‐Relaxation (PIRAT). Issue 5 (25th January 2018) - Stadler, Eduard; Dommaschk, Marcel; Frühwirt, Philipp; Herges, Rainer; Gescheidt, Georg
Abstract: Increasing the signal‐to‐noise ratio is one of the major goals in the field of NMR spectroscopy. In this proof of concept, we accelerate relaxation during an NMR pulse sequence using photo‐generated paramagnetic states of an inert sensitizer. For the follow‐up acquisition period, the system is converted to a diamagnetic state. The reversibility of the photo‐induced switching allows extensive repetition required for multidimensional NMR. We thus eliminate the obstacle of line‐broadening by the presence of paramagnetic species. In this contribution, we show how cycling of synchronized light/pulse sequences leads to an enhanced efficiency in multidimensional NMR. Our approach utilizes a molecular spin switch reversibly altering between a paramagnetic and diamagnetic state. Abstract : A light‐switchable molecular magnet is used to change the longitudinal relaxation rate during applied NMR pulse sequences with in situ irradiation of the NMR sample. The results could encourage the use of light‐driven switchable molecular magnets in NMR spectroscopy.